Association between free nutritious meal consumption and nutritional status in elementary school children - Afindo Dedy Permana; Warsiti Warsiti; Yuni Purwati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The Free Nutritious Meal Program is a government initiative aimed at improving the health and nutritional status of the population. However, the provision of nutritious meals through this program does not automatically lead to improvements in nutritional status. The success of the Free Nutritious Meal Program requires sustained and appropriate healthy eating behaviors among beneficiaries. Purpose: To analyze the relationship between nutritious food consumption behavior and the nutritional status of students Elementary School who are beneficiaries of the Free Nutritious Meal Program. Method: This study employed an analytical correlational design with a cross-sectional approach. The sample consisted of 241 students from grades 1 to 6. Data were collected using a nutritious food consumption behavior questionnaire and nutritional status measurements. Statistical analysis was performed using Spearman’s rank correlation test. Results: Most students demonstrated good nutritious food consumption behavior (64.7%). The majority had normal nutritional status (59.8%), with a mean BMI-for-age Z-score of 0.67 ± 1.59. Spearman’s rank correlation analysis showed a correlation coefficient of 0.103 with a significance value of p = 0.109 (p > 0.05). Conclusion: There was no statistically significant relationship between nutritious food consumption behavior and the nutritional status of students at Gedongkiwo Elementary School. However, based on school records prior to receiving the Nutritious Meal Program program, 11 students who were at risk of stunting, 20 students who were underweight, and 4 students who experienced wasting had achieved normal nutritional status at the time of the study. Suggestion: These findings should be interpreted with caution, as the cross-sectional design does not allow for the observation of changes in nutritional status before and after the implementation of the Free Nutritious Meal Program. Further longitudinal studies or studies that consider students' baseline nutritional status are recommended